Réponses

2014-04-13T11:56:16+02:00
3(2x+5) = -7(3-2x)
6x+15 = -21+14x
6x -14x = -21 -15
-8x = -36
x = -36/ -8
x= 9/2

(2x+1)(5-6x) = -3x(4x-1)
10x-12x²+5-6x = -12x²+3x
4x-12x² +12x² -3x = -5
x =-5
2014-04-13T14:06:53+02:00
Salut :)

3(2x+5) = -7(3-2x)

6x + 15 = -21 + 14x
6x + 15 - 14x = -21
-8x + 15 = -21
-8x = -21 - 15
-8x = -36
x = -36/-8
x = 4.5

(2x+1)(5-6x) = -3x(4x-1)

10x - 12x² + 5 - 6x = -12x² + 3x
-12x² + 4x + 5 = -12x² + 3x
-12x² + 4x + 5 + 12x² = 3x
4x + 5 = 3x
5 = 3x - 4x
5 = -x
x = -5

J'espère t'avoir aidé(e) ! :)